Cover Image, Volume 30, Issue 11. Issue 11 (24th October 2020) - Ecker, András; Romani, Armando; Sáray, Sára; Káli, Szabolcs; Migliore, Michele; Falck, Joanne; Lange, Sigrun; Mercer, Audrey; Thomson, Alex M.; Muller, Eilif; Reimann, Michael W.; Ramaswamy, Srikanth
Abstract : Cover legend: The cover image is based on the Research Article Data‐driven integration of hippocampal CA1 synaptic physiology in silico by András Ecker et al., https://doi.org/10.1002/hipo.23220 . Illustration Credit: Caitlin Monney at Blue Brain Project.